Pengukuran Kualitas untuk Aplikasi Permainan pada Perangkat Bergerak berdasarkan ISO 9126 - Galang Amanda Dwi P.; R. Firman Insan M.; Siti Rochimah (ULTIMA InfoSys, 2014)
Today, the rise of the mobile game applications development is a major phenomenon in the development of the mobile technology. Along with those trends, there are studies related to the development of a mobile game which expect the development of mobile games can be better in terms of quality and a higher tendency on the market. One of the things that is crucial to determine the quality of a game application on mobile devices is the standard calculations and metrics. In this paper a framework to measure the quality of a game application on mobile devices based on the ISO 9126 standard is proposed. The characteristics of the ISO 9126 standard will be mapped to the characteristics possessed by the mobile game applications, and by using the Analytic Hierarchy Process, the significance value to each aspect the game application can be obtained and the metric can be built Index terms - Analytic Hierarcy Process, Game Application, Mobile Devices, ISO 9126, Software Quality Management